RESEÑA DE: Miranda García, Fermín, Breve Historia de los Godos. - Jiménez Garnica, Ana Mª (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2016)
RESEÑA DE: Miranda García, Fermín, Breve Historia de los Godos. Madrid. Editorial Nowtilus, 2015. 276 págs. isbn: 978-84-996-7736-1.